BIG DATA AND SUSTAINABLE DEVELOPMENT OBJECTIVES - Raluca, Dumitru (Annals of Spiru Haret University. Economic Series, 2022)
Abstract Most scientific fields explore the perspectives of digital applications. In the digitalization process, Big Data offers us new ideas and methods to understand the Earth and undertake the epic mission of sustainable development with a new impetus. Big Data offers us new ideas and methods to understand the Earth and undertake the epic mission of sustainable development with a new impetus.